Prevalensi Buta Warna Pada Calon Mahasiswa yang Masuk di Universitas Tadulako - Sumarni Sumarni (Biology Department, Mathematics and natural science, Tadulako University, 2010)
Color blindness is a condition in which certain colors can not be distinguished, and most often caused by a hereditary disease. The purpose of this study to determine the prevalence of color blindness on prospective students who enrolled in the University Tadulako. Data collection was performed by means of color-blind investigation on every applicant that comes a medical examination at the Polyclinic Bungamputi Tadulako University. From the results, the prevalence of color blindness on prospective new students Tadulako University is 1.27% consisting of male and female 0.87% 0.40%. Key words: Color blindness, prevalensi.